Perinatal Potential Hazards of Hepatitis; a Tertiary Care Study - Aisha Ambreen; Hussain, Asim; Bano, Naheed; Afsheen, Nadia; Tarar, Muhammad Haseeb Anwar; Iqbal, Mazhar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore the frequency of HEV infection in pregnancy, associated risk factors and its prenatal and maternal consequences. Study Design: Prospective longitudinal study Place and Duration of Study: Department of Gynaecology Obstetrics, Divisional Head Quarter Hospital, Multan, Pakistan from Nov 2021 to Jun 2023. Methodology: The research comprised 100 patients, 50 pregnant patients who met the criteria for eligibility. For seroprevalence, anti-HEV antibodies (IgG) were detected. Hepatic profile, CBC, coagulation markers, and standard workup/protocol were also assessed for prenatal fetomaternal hemorrhage. Results: Data was gathered using pre-designed questionnaires. Of the 50 patients, 31 (62%), were HEV positive with mean age 26.90±4.16 year. Serum bilirubin levels >1.5 mg/dL in 47 patients (94.00%) with SD1.68±0.28, AST (SD85.87±51.878), ALT (SD149.42±71.90) in 38 (76.00%), low platelet count in 24 cases. There were 6 cases (9.35%) IUD, 3 (8.75%) fetal distress and 4 (12.09%) maternal distress, preterm deliveries 4 (12.09%) and 3(2.5%) neonatal deaths. Mortality rate was (38.7%) 12 cases, due to hepatic comma and intravascular coagulation and Fulminant hepatic failure. Conclusion: Hepatitis E (HEV) infection during gestation may result in serious consequences such as elevated hepatic profiles, acute anemia, low platelet count, IUD, premature delivery, and postpartum issues, which are primarily caused by inadequate sanitation and a contaminated water source. Maternal fatalities and fetal consequences are exacerbated by HEV infection.